Harmful Algal Bloom Impacts on Human Health: An Analysis of National Emergency Department Data in the U.S. from 2016 to 2018 - French, Benjamin (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF To see the formatted meeting abstract.